2017
DOI: 10.1002/ar.23729
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effect of Curcumin and Methylprednisolone in the Rat Spinal Cord Injury

Abstract: In addition to imperiling an individual's daily life, spinal cord injury (SCI), a catastrophic medical damage, can permanently impair an individual's body function. Methylprednisolone (MP), a medically accepted therapeutic drug for SCI, is highly controversial for the lack of consensus on its true therapeutic effect. In recent years, curcumin has served as a potential and novel therapeutic drug in SCI. Our study was intended to investigate the precise effect of MP and curcumin in SCI. We examined the function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…We previously reported curcumin to have a better therapeutic potential than MP with prolong treatment time between 14 and 35 days following SCI (Liu et al, ). These natural substances seem to have a promising therapeutic potential in SCI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported curcumin to have a better therapeutic potential than MP with prolong treatment time between 14 and 35 days following SCI (Liu et al, ). These natural substances seem to have a promising therapeutic potential in SCI.…”
Section: Discussionmentioning
confidence: 99%
“…MP has been evinced to reduce neuroinflammation and relieve SCI complications associated with the mechanisms of secondary injury. However, the use of MP is highly controversial owing to non-reproducibility of its beneficial effects as well as unwanted side effects (Evaniew et al, 2016;Liu et al, 2017;Shroff & Gupta, 2015). The American Association of Neurological Surgeons in their guidelines no longer recommend MP usage for the management of acute SCI (Cabrera-Aldana et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin, (1E,6E)-1,7-bis(4-hydroxy-3methoxyphenyl)hepta-1,6-diene-3,5-dionealso known as diferuloylmethane Figure 1, is a phenolic compound 1 present in many kinds of medicinal plants, especially in Curcuma longa (turmeric) 2 , and was first discovered and isolated in 1815 by Harvard College laboratory scientists Vogel and Pelletier 3 . The first article referring to the use of Curcumin in human diseases was published in 1937 4 .Curcumin possesses many pharmacological activities including antioxidant, anti-infection, anti-inflammation, anti-Alzheimer and anticancer [5][6][7][8][9][10][11][12][13][14][15][16][17][18] . Curcumin is a special spice which is the functional ingredient in curry powder 19 , and a potential natural food coloring 20 ; it impairs an attractive yellowish-orange color to food, authorized as a food additive by the Joint FAO/WHO Expert Committee on Food Additives (JECFA) in 1974, it's E number is E 100 21 .…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that all these stages possess certain therapeutic effects. In our precursory study, curcumin was found to have the capability of serving as a future therapeutic for SCI [ 8 ]. It is worth noting that one of the chief targets in SCI treatment is to improve the microenvironment and promote the regeneration of the injured site.…”
Section: Introductionmentioning
confidence: 99%